Organizational Resilience in Times of Crisis: Its Relation with Work-Life Balance and Work Engagement - Novianti, Khusnul Rofida; Arifiani, Ratya Shafira; Pratika, Yeyen (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2024)
Various studies have recognized the importance of the resilience aspect for individuals to be able to rise and overcome all challenges, especially the Covid-19 pandemic. One of the important aspects for individuals to be able to survive is the aspect of balance between personal and work-life balance (WLB). On the other hand, this aspect of WLB is also a determining factor for individual engagement with the organization (work engagement) so that employees can be loyal to the organization. For this reason, this study aims to examine the work-life balance and organizational resilience to work engagement for employees who work from home during the Covid-19 pandemic. This study uses an explanatory quantitative approach with data collection methods using questionnaires that will be distributed online and processed using Partial Least Square (PLS) using 130 respondents. The results showed a positive and significant effect between the work-life balance on work engagement, work-life balance on organizational resilience, and organizational resilience on work engagement. The results also show the mediating role of organizational resilience on the effect of work-life balance on work engagement.